Micromorphology, pharmacognosy, and bio‐elemental analysis of an important medicinal herb: Verbascum thapsus L. Issue 6 (6th February 2020) - Khan, Shafqat Ali; Dastagir, Ghulam; Uza, Noor Ul; Muhammad, Akhtar; Ullah, Rahim
Abstract: The present study was conducted on characterization of morpho‐anatomical, phytochemical, and bio‐elemental analysis of root, stem, and leaf of Verbascum thapsus . Morphologically Verbascum is a biennial plant that flowers for a month and a half in mid‐ to late summer. Various organoleptic features of root, leaf, and stem were recorded. Anatomically the T. S of the root, stem, and leaf showed a typical dicot histological differentiation. Leaf possessed anomocytic stomata, crescent shape vascular bundles, and covered with long and stellate type trichomes while, stem contained collateral type of vascular bundles and a well‐developed pith to store phytochemicals responsible for various pharmacological activities. The powder drug study through scanning electron microscopy revealed the presence of various types of tissues. Branched, tree like and stellate trichomes in root and leaf help in absorption and reduce loss of water. These anatomical features are responsible for the survival of the plant as biennial. Four macro elements (Na, K, Ca, and Mg) and seven microelements (Cr, Cu, Fe, Mn, Ni, Zn, and Cd) and their concentrations in ppm were also studied using Atomic Absorption Spectroscopy. Phytochemical screening of methanolic extract showed existence of various secondary metabolites, while mucilage and anthraquinones was not detected. The present study helps to understand the taxonomic identification of the plant based on morpho‐anatomical features and throws the attention of the researchers to carry out the work for developing its various formulations, which can ultimately be beneficial for the human beings as well as animals. Abstract : The present study was conducted on characterization of morpho‐anatomical, phytochemical, and bio‐elemental analysis of Verbascum thapsus . Morphologically Verbascum is a biennial plant that flowers for a month and a half in mid‐ to late summer. Anatomically the T. S of the root, stem, and leaf showed a typical dicot histological differentiation. All parts except root were covered with trichome hairs that were mostly long and stellate type. Leaf possesses anomocytic stomata and crescent shape vascular bundles while, stem contained collateral type of vascular bundles. Four macro bio‐elements (Na, K, Ca, and Mg), seven microelements (Cr, Cu, Fe, Mn, Ni, Zn, and Cd) and various phytochemical and their concentrations were detected. The present study helps to understand the morphological and anatomical aspects of the plant and also helps in the taxonomic identification of the plant based on morphological and anatomical features. The multiple benefits of V. thapsus made it a true miracle of nature. It elicits on all the aspects of the herb and throws the attention to set the mind of the researchers to carry out the work for developing its various formulations, which can ultimately be beneficial for the human beings as well as animals.